PENANAMAN MODAL ASING MEMBAWA DAMPAK LIBERALISASI TERHADAP PEREKONOMIAN NASIONAL - Kamal, Fahmi (www.bsi.ac.id, 2014)
Foreign investment in Indonesia has been going on since Dutch colonial times to the present . Foreign investment will affect the joints - joints economy in our country , among others, the presence of foreign investors the sector - a sector of the economy in our country will grow. With the growing sectors - sectors of the economy in our country , it will bring the impact of liberalization on the national economy . This means that the sector - the economy will grow and flourish . The presence of foreign investors is expected to bring a change in the sector - the sector of the national economy such as funding , technology , and expertise . It is expected that the government can play an active role in utilizing foreign investment to facilitate access into the world of business in Indonesia but without marginalizing local entrepreneurs . Foreign capital inflows ( capital inflows ) play a role in closing the income gap caused by a deficit in the current account . In addition , the influx of foreign capital is also able to drive the economic activity slow due to lack of capital ( investment- saving gap ) for the implementation of economic development . This foreign capital than as a capital transfer can also make a positive contribution through the flow of industrialization and modernization . In the short term , foreign debt greatly assist the Indonesian government in an effort to close the budget deficit of income and expenditure, due to finance routine expenditure and development expenditure is quite large. Thus, the rate of economic growth can be driven in accordance with predetermined targets . Keywords: foreign investment, liberalization, the national economy